ACHIEVEMENT MOTIVATION COUNSELING TO INCREASE THE PERFORMANCE OF DIFABEL SLAWI MANDIRI MEMBERSHIP - Sri Adi Nurhayati; Sesya Dias Mumpuni (Universitas Muhammadiyah Semarang, 2018)
Education in Indonesia has a very wide scope. Apart from teaching and learning in the classroom, guidance and counseling is one component of education. The scope of cross-cultural counseling is wide-ranging, such as across cultures of the elderly, with disabilities, men, women, bourgeois, spiritual, and multiethnic. But this time more understanding of cross-cultural in the disable. This is because difable has a very extraordinary advantages compared with others. Limitations are not a barrier to continuing to struggle through life. This self-condition isfound in case studies on disabling performance in the Difabel Slawi Mandiri (DSM) organization in the Tegal. This indicates the acceptance needed by the disabled to be able to re-interact and continue his life especially to start a job. Counseling is needed to be able to help the disabled in determining the goals of self. Respondents from qualitative research of special case study took one counselee. The data comes from a snowball samplinginterview that informs a particular respondent who has a case in performance. Performance indicators, among others, appear (1) task behaviors , (2) task performance , (3) productivity and (4) quality on the self of the counselee . From these indicators states the observation and interview results are low. Counseling was conducted for six times. Counseling meetings are: (1) attending, (2) agreeing on counseling purposes, (3) treatment agreement, (4) treatment application, (5) counsel evaluation and (6) termination. Counseling series isdone by the counselee well. Effects that the counselee feels can help in relationships with colleagues and within himself. Without a strong determination the counselee does not succeed in counseling. Achievements are no less successful than those who work hard for the present and future life. Keywords: counseling, counseling process, education, case study, qualitative